Spaces of care - Spaces of Care: Socio-Legal Workshop (2018 : University of Cambridge); Gelsthorpe, Loraine; Mody, Perveez; Sloan, Brian, 1984-; Cambridge Socio-Legal Group (Oxford [England] : Hart, 2018)
"This collection interrogates the ways in which the emerging interdisciplinary study of care challenges and provokes a reassessment of the points of connection and disjuncture between care and governance, ethics and public, personal and professional identities. The volume emerges from a project coordinated by the Cambridge Socio-Legal Group. It brings together leading international scholars to discern and articulate what we may consider to be a useful analytic of care. Lawyers, anthropologists, sociologists and criminologists reflect on specific aspects of conceptualising caring relations in 'spaces' including communities of care and abandonment, self-care and kinship care, spaces as 'gaps' in care, the meanings of marketised care, and the ways in which care is constructed and constrained in different ways in venues such as homes, prisons, workplaces and virtual spaces. Common themes cut across the chapters. These include: temporality (historical specificity) and the dynamics of care across time and place; subjectivity - are intentions of care experienced in that way? What does care feel like?; the economies of care (including the commodification of care; public and private manifestations of care; privatised 'care'); disruptions of care - which generate vulnerabilities with regards to continuities of care; eligibility - those deemed to be deserving and undeserving of care; relationalities of care (collective and individual agency in caring relations, kinship care), and technologies and imaginaries of care - as in new notions of care forged by those in online virtual worlds such as Second Life"--
Introduction : Spaces of Care : Concepts, Configurations, and Challenges / -- Loraine Gelsthorpe, Perveez Mody and Brian Sloan -- Punishment and Care Reappraised / Rob Canton and Jane Dominey -- Who Cares? : Probation Practice and Privatisation / Jane Dominey and Loraine Gelsthorpe -- Paradoxes of Care : Women in the Criminal Justice System in England and Wales / Loraine Gelsthorpe and Rob Canton -- 'All Children are Our Children' : Care and Kinship in Residential Children's Homes in the Russian Federation / Elena Khlinovskaya Rockhill -- Re-imagining Cities as Spaces of Care : A Perspective from -- Street Homelessness / Helen Carr, Ed Kirton-Darling and Maria Fernanda -- Salcedo Repolês -- Formal and Informal Care in the Public and Private Spheres in England and Australia / Brian Sloan -- Care and the Workplace : The Dutch Approach to Part-time Work, Flexible Working Arrangements and Leave / Susanne Burri -- Ethics of Care and Disability Rights : Complimentary or Contradictory? / -- Jonathan Herring -- Kinship Care / Perveez Mody -- Home and Away: Mobility and Care in Botswana's Time of AIDS / Koreen M Reece -- Witnessing, Containing, Holding? : The German Social Welfare State -- (Sozialstaat) and People in Flight / John Borneman -- The Ability of Place: Digital Topographies of the Virtual Human on Ethnographia Island / Tom Boellstorff.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Social legislation -- Congresses; Law,Family law; Electronic books